2013
DOI: 10.1093/mnras/stt2006
|View full text |Cite
|
Sign up to set email alerts
|

The RMS survey: galactic distribution of massive star formation★

Abstract: We have used the well-selected sample of ∼1750 embedded, young, massive stars identified by the Red MSX Source (RMS) survey to investigate the Galactic distribution of recent massive star formation. We present molecular-line observations for ∼800 sources without existing radial velocities. We describe the various methods used to assign distances extracted from the literature, and solve the distance ambiguities towards approximately 200 sources located within the Solar circle using archival H i data. These dist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
125
1
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(145 citation statements)
references
References 89 publications
18
125
1
1
Order By: Relevance
“…Although there are a number of massive star-forming regions associated with the Sagittarius arm, the star formation per unit area is relatively modest when compared to the segments of the spiral arms located inside the Solar circle. This is in stark contrast to the high surface density of MYSOs and compact H ii regions reported by Urquhart et al (2014b) found to be associated with the Sagittarius arm and its association with RCW42, NGC3603 and G282.0−1.2 (Carina), which are some of the most active star-forming complexes in the Galaxy.…”
Section: Galactic Distributioncontrasting
confidence: 89%
See 3 more Smart Citations
“…Although there are a number of massive star-forming regions associated with the Sagittarius arm, the star formation per unit area is relatively modest when compared to the segments of the spiral arms located inside the Solar circle. This is in stark contrast to the high surface density of MYSOs and compact H ii regions reported by Urquhart et al (2014b) found to be associated with the Sagittarius arm and its association with RCW42, NGC3603 and G282.0−1.2 (Carina), which are some of the most active star-forming complexes in the Galaxy.…”
Section: Galactic Distributioncontrasting
confidence: 89%
“…itudes (i.e., |b| < 5 • ), also found a low number of MYSOs and compact H ii regions associated with the arms located in the third quadrant (Urquhart et al 2014b). This suggests that little massive star formation is taking place in the outer parts of the Galaxy compared to the inner Galaxy or that star formation in spiral arms is patchy and/or intermittent (Urquhart et al 2014b).…”
Section: Galactic Distributionmentioning
confidence: 92%
See 2 more Smart Citations
“…This information makes it possible to integrate the trajectory of the binary ⋆ E-mail: imandel@star.sr.bham.ac.uk backwards in the Galactic potential until it intersects the Galactic plane, where the binary is assumed to have been born. This assumption is consistent with both the observed birth locations of massive stars in a thin disk in the Galactic plane (e.g., Urquhart et al 2014), and more specifically the finding that metal abundances in the secondary in blackhole X-ray binaries is consistent with a thin-disk origin (e.g., González Hernández et al 2008). Population synthesis modeling can then be applied to include the contribution of Blaauw kicks (Blaauw 1961) from mass loss during the supernova and constrain the range of supernova-induced natal kicks required to preserve the binary with current orbital parameters.…”
Section: Introductionsupporting
confidence: 89%